(untitled) (Swiss Medical Weekly, 2024)
OBJECTIVES: Due to the increasing complexity of the healthcare system, effective communication and data exchange between hospitalists (in-hospital physicians) and primary care physicians (PCPs) is both central and challenging. In Switzerland, little is known about hospitalists’ perception of their communication with PCPs. The primary objective was to assess hospitalists’ satisfaction with their communication with PCPs. Secondary objectives addressed all information about the referral process and communication with PCPs during and after the hospital encounter. Lastly, the results of a previous survey among PCPs were juxtaposed to compare their responses to similar questions. METHODS: This study surveyed hospitalists in six hospitals in the Central Switzerland region. The survey was sent via email to hospitalists from November 2021 to February 2022. The questionnaire contained 17 questions with single- and multiple-choice answers and the option of free-text entry. Exploratory multivariable logistic regression was used to analyse independent associations. RESULTS: In total, 276 of 1134 hospitalists responded (response rate 24.3%): (1) the majority of hospitalists are satisfied with the general communication (n = 162, 58.7%) as well as with referral letters (n = 145, 52.5%), (2) preferred information channels for referral letters are email (n = 212, 76.8%) and electronic portals (n = 181, 65.5%), (3) the three most important items of information in referrals are: medication list, diagnoses and reason for referral. In multivariable regression, compared to other clinicians, internists independently favoured informing PCPs of emergency admissions of their patients in a timely manner (OR 2.04; 95%CI 1.21–3.49). Comparing responses from PCPs (n = 109), the most prominent discrepancy was that 67% (n = 184) of hospitalists claimed to “always” inform after an encounter, whereas only 7% (n = 8) of PCPs agreed. CONCLUSION: Most hospitalists are satisfied with the communication with PCPs and prefer electronic communication channels. Room for improvement was found around timely transmission of patient information before and after hospital encounters.